ANALISIS PENGARUH PENGALAMAN DAN PENGGUNAAN INTUISI AUDITOR DALAM MENDETEKSI KEKELIRUAN - Wuisan, Novitha Rosaliana Mariane; Poputra, Agus T.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Accounting profession is aprofession that is based on the public trust. But with the case - the case of the financial statements and the disclosure of the indicator solutions between the public account firm and its clien in order to qualify to go public that the commmunity is not fully confident in the accounting profession. Institutional background and different laws that distinguish public sector audit by the private sector, where public sector auditing procedures and have different responsibilities and a broader role than the private sector audit. It can be seen that govemment auditor in carrying out their duties not only examine and assess the fairness of the financial statment of the public sector but also govemmen officials to assess compliance laws - laws and regulations. Purpose of this study was determine the effect of auditor experience and use intuition in detecting errors in the North Sulawesi Provincial Inspectorate. Methodes of analysis used in this study is multiple regression analysis. Result showed that experience and use intuition influential auditors in detecting errors in the North sulawesi Provincial Inspectorate. Multiple correlation analysis shows that the relationship between the variables of experience and use intuition auditors in detecting errors in the North Sulawesi Provincial Inspectorate strong enough.